PERFORMANCE OF SESAME (SESAMUM INDICUM L.) VARIETIES AS AFFECTED BY ORGANIC AND INORGANIC FERTILIZERS IN BILLIRI, GOMBE STATE AND MAKURDI BENUE STATE NIGERIA - Nwanojuo, M. N.; Madina, Paul (FUDMA JOURNAL OF SCIENCES, 2021)
Field experiment was carried out during the rainy season of 2019 in Tal, Billiri Local Government, Gombe State and Teaching and Research farm University of Agriculture Makurdi Benue State. The aim of the experiment was to investigate the performance of five varieties of sesame under organic and inorganic fertilizer. Treatments consisted of five varieties of sesame (E-8, NCRIBEN-01, NCRIBEN-02, NCRIBEM-031 and YANDEV-55) and five fertilizers (NPK, Poultry dropping, cow dung, goat manure and control). These were factorially combined and laid in a randomized complete block design with three replications. The results of the study revealed that sesame generally responded to both varietal, fertilizer and location effects. All the parameters studied have significantly (Pâ‰¤0.05) responded to the both varietal, fertilizer and location effects where variety NCRIBEN-01 and E-8 was observed to perform higher in both growth character and grain yield. NPK fertilizer and Benue location was significant in both growth, yield related character and overall yield. Based on the result obtained it can be suggested that the use of E-8, NCRIBEN-01 and NPK fertilizer will lead to optimum yield for farmer in Billiri local Government, Gombe state and Benue State Nigeria
Keywords: varieties, organic source of nutrient or organic fertilizer, inorganic fertilizer